Analyzed of Convection Heat Transfer in Cabin Car Equipped With Air Conditioner (AC) Using A Simple Method Assisted by Microsoft Excel - Asmoro, Langgeng; Humami, Faris; Hakim, Iman Nur (RSF Conference Series: Engineering and Technology, 2022)
Visualization of heat flow often uses complex and challenging programs such as Matlab and Ansys Fluent with expensive licenses, and the operation is also difficult. This study aims to demonstrate the phenomenon of convection heat transfer in a simple way. The phenomenon of convection is fairly difficult, and the heat transfer process can cause misconceptions in students. An appropriate and easy-to-use method is needed in preparing for classroom learning. This study was conducted to review the air condition in the car cabin, which is influenced by airflow from the air conditioner, and visualize it. This visualization can be used to explain the phenomenon of heat transfer by convection to students, especially while cooling the car’s air conditioner. This research was conducted using a car model with three rows of seats where the air conditioner is only on the front cabin dashboard. On the dashboard, the AC flows are located on the left, right, and center. The calculation is carried out by applying the Black Principle, where other particles around it influence the particle temperature. Microsoft Excel is used to perform mathematical operations and visualize the results in graphs. It successfully delivers a 2D image showing heat distribution in the car cabin space. Visualization of this convection phenomenon can provide an overview of the convection flow phenomenon. So, this method is very easy to operate and apply by teachers in preparing lessons on the phenomenon of temperature convection.